Evaluation of unfractionated heparin versus low‐molecular‐weight heparin and fondaparinux for pharmacologic venous thromboembolic prophylaxis in critically ill patients with cancer. (15th November 2018) - Van Matre, E. T.; Reynolds, P. M.; MacLaren, R.; Mueller, S. W.; Wright, G. C.; Moss, M.; Burnham, E. L.; Ho, P. M.; Vandivier, R. W.; Kiser, T. H.
Abstract : Essentials Critically ill cancer patients require pharmacologic prophylaxis for venous thromboembolism (VTE). Patients from 566 hospitals in the United States between 2010 and 2014 were included. Low‐molecular‐weight heparin (LMWH) prophylaxis was not associated in a reduction of VTE rates. LMWH prophylaxis was associated with a reduction in bleeding and heparin induced thrombocytopenia. Summary: Background: Critically ill patients with cancer are at increased risk of venous thromboembolism (VTE) from physical and cellular factors, requiring pharmacologic prophylaxis to reduce the risk of VTE. Objectives: To assess whether low‐molecular‐weight heparin (LMWH) prophylaxis reduces in‐hospital rates of VTE or improves clinical outcomes compared with unfractionated heparin (UFH) prophylaxis in critically ill patients with cancer. Methods: We used a propensity‐matched comparative‐effectiveness cohort from the Premier Database. Patients aged 18 years or older with a primary diagnosis of cancer, intensive care unit admission and VTE prophylaxis within 2 days of admission between 1 January 2010 and 31 December 2014 were included. Patients were divided into LMWH or UFH prophylaxis groups. Results: A total of 103 798 patients were included; 75 321 (72.6%) patients received LMWH and 28 477 (27.4%) patients received UFH. Propensity analysis matched (2 : 1) 42 343 LMWH patients and 21 218 UFH patients. Overall, LMWH was not associated with a decreased incidence of VTE (5.32% vs. 5.50%). LMWH prophylaxis was associated with a reduction in pulmonary embolism (0.70% vs. 0.99%), significant bleeding (13.3% vs. 14.8%) and heparin‐induced thrombocytopenia (HIT) (0.06% vs. 0.19%). In non‐metastatic solid disease, LMWH was associated with decreased VTE (4.27% vs. 4.84%) and PE (0.47% vs. 0.95%). Conclusions: The use of an LMWH for VTE prophylaxis was not associated with a reduction in the incidence of in‐hospital VTE as compared with UFH, but was associated with significant reductions in PE, clinically important bleeding events, and incidence of HIT in critically ill patients with cancer.